Pay gaps in the National Health Service: Gender and sexuality - Karen Ann Mumford; Edith Aguirre; Anna Einarsdöttir; Bridget Lockyer; Melisa Sayli; Benjamin Arthur Smith (PLoS ONE, 2026)
Studies investigating the relationship between gender, sexual identity and pay have increased in number and scope over the last three decades, enabling a greater understanding of the outcomes facing LGB+ workers in the labour market. Pay gap studies that also allow for the disclosure of sexual identity in the workplace are, however, very rare. Using a rich survey of employees from the National Health Service in England, this article considers the relationship between relative pay, LGB+ identity, and disclosure for both men and women. While the findings reveal substantial heterogeneity within the LGB + , disclosure is shown to be related to higher pay from larger returns on the endowments of LGB+ employees (men or women), especially so for men.